The urgency of implementing the maṣlahah theory as a basis for halal sport tourism: A study on the organization of marathons (Case in Borobudur Marathon) - Fithri Dzikrayah; Ahmad Hasan Ridwan; Nurrohman Syarif (Journal of Halal Science and Research, 2026)
This study contributes to the literature on halal tourism by introducing maṣlahah theory as a normative framework for halal sport tourism, particularly in marathon organization. It expands the application of maṣlahah into the sport tourism context and provides conceptual guidance for organizing marathons that promote public benefit, ethical values, participant safety, and socio-economic sustainability. Marathons, as part of sports tourism, are seen not only as sporting activities but also as having significant potential to strengthen the halal tourism sector. This study is based on the fact that there are still marathon events that do not fully meet Sharia standards, both in terms of worship facilities, halal consumption, and event management. Using a descriptive qualitative approach, this study examines the application of maṣlahah theory as a conceptual basis in integrating maq values.USid al-sharī'ah into the practice of halal sports tourism. The results of the analysis indicate that the value of maṣlahah can be implemented in three main dimensions: first, the economic dimension through the empowerment of MSMEs and the multiplier effect on the local tourism sector; second, the social dimension through community involvement, volunteers, and strengthening social cohesion based on local culture; third, the spiritual dimension through the provision of worship facilities, halal consumption, and the avoidance of non-halal elements in events. In addition, applying the green sport event concept also strengthens the value of maṣlahah in environmental aspects. These findings confirm that maṣlahah can be a strategic paradigm for directing sports tourism not only as entertainment but also as a means of economic empowerment, community participation, and strengthening spiritual values. Keywords: Halal sport tourism; Maqāṣid al-sharī‘ah; Marathon events; Maṣlahah; Sustainable tourism.